Application of Hemifield Visual Electrophysiology to Diagnose Functional Vision Loss. Issue 4 (December 2020) - Moss, Heather E.; Jabbehdari, Sayena
Abstract : Abstract: Neuro-ophthalmologists frequently see patients who are experiencing vision loss not accounted for by a neuro-ophthalmic disorder. In this article, we describe a case of binasal hemianopia in an otherwise healthy 65-year-old woman who was initially diagnosed with glaucoma but ultimately proved to have functional visual loss. This diagnosis was made by confirming by confirming normal visual pathway function using hemifield visual-evoked potential studies.